2013
DOI: 10.1136/gutjnl-2013-304623
|View full text |Cite
|
Sign up to set email alerts
|

In vitro infection of primary human hepatocytes by HCV-positive sera: insights on a highly relevant model

Abstract: We identified critical factors leading to efficient PHH infection by HCV sera in vitro. Overall, we showed that this cellular model provides a useful tool for studying the mechanism of HCV infection in its natural host cell, selecting highly infectious isolates, and determining the potency of drugs towards various HCV strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Moreover, APC expression in cancer cells causes nuclear and cytoplasmic translocation of b-catenin to the cell membrane (Aoki and Taketo, 2007). The increase of APC mRNA expression in parallel with PHHs adhesion and polarization (Gondeau et al, 2014) could contribute to WNT/b-catenin pathway down-regulation in PHHs (Hanson and Miller, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, APC expression in cancer cells causes nuclear and cytoplasmic translocation of b-catenin to the cell membrane (Aoki and Taketo, 2007). The increase of APC mRNA expression in parallel with PHHs adhesion and polarization (Gondeau et al, 2014) could contribute to WNT/b-catenin pathway down-regulation in PHHs (Hanson and Miller, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A multiplex profiling of cytokines and growth factors in serum samples from HCV-infected patients has shown that at least 24 cytokines and growth factors affect the change in hepatocyte biology and the efficiency of the infection process [4]. At the same time, only limited data are available for the roles particular regulators of immune reactions play in hepatitis C at the cell level (in infected liver cells).…”
Section: Introductionmentioning
confidence: 99%
“…PHHs isolated from patient biopsies have been used to study HCV infection in vitro [53,146152]. However, these cells suffer from limited accessibility, variability between batches, a finite culture time and low levels of infection with the standard HCVcc strains.…”
Section: Keeping the Pieces In Place: Role Of The Tight Junction In Ementioning
confidence: 99%